Development of a scale to measure skepticism toward electronic word-of-mouth. (March 2016) - Zhang, Xiao (Jerry); Ko, Myung; Carpenter, Darrell
Abstract: In recent years, electronic word-of-mouth (eWOM) has become an influential factor affecting Internet users' perceptions and behaviors (Chatterjee 2001; Lee et al. 2009). However, as more evidence demonstrating the utilization of fake eWOM has been discovered (Forrest and Cao 2010; Malbon 2013), Internet users' trust of eWOM may have been severely undermined, and they may have developed skepticism about this kind of communication in general. Current measurement scales for evaluating Internet users' suspicions/distrust toward eWOM messages are adopted from the marketing discipline and developed for advertising skepticism, which is contextually different from skepticism toward eWOM. The purpose of this study is to create a new measurement scales for eWOM skepticism. Using data from a preliminary survey, new measurement items for eWOM skepticism were established. Then, the new items were validated using a second survey dataset. The reliability and validity of the new scales suggested that the new instrument is suitable for measuring eWOM skepticism. This study contributes to the eWOM literature by highlighting the importance of investigating eWOM situations from the perspective of suspicion and distrust.